2022
DOI: 10.1088/2632-072x/ac52e6
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocity, community detection, and link prediction in dynamic networks

Abstract: Many complex systems change their structure over time, in these cases dynamic networks can provide a richer representation of such phenomena. As a consequence, many inference methods have been generalized to the dynamic case with the aim to model dynamic interactions. Particular interest has been devoted to extend the stochastic block model and its variant, to capture community structure as the network changes in time. While these models assume that edge formation depends only on the community memberships, rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 31 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…Such a condition could in principle be relaxed following the approaches of refs. 53 55 , we do not explore this here.…”
Section: Resultsmentioning
confidence: 99%
“…Such a condition could in principle be relaxed following the approaches of refs. 53 55 , we do not explore this here.…”
Section: Resultsmentioning
confidence: 99%
“…As accurately identifying anomalies is deeply connected with the chosen null model determining what regular patterns are, it is important to consider other possible mechanism for tie formation, beyond community structure. In recent works [31][32][33], we found that modeling community patterns together with reciprocity effects, leads to higher predictive performance, thus more expressive generative models. This could significantly change the performance of our foundational model as well.…”
Section: Discussionmentioning
confidence: 86%
“…Yasami Y et al [15] noted information that related to the dynamic features of node interactions, analyzed the properties of multilayer networks, and modeled the evolution of network topologies at different layers by an infinite factorial hidden Markov model of feature cascades. Safdari et al [16] noted the importance of additional parameters that captured structural properties. Therefore, they presented a probabilistic generative model that integrated these parameters and network communities as structural information.…”
Section: B Probability Models-based Link Predictionmentioning
confidence: 99%